2019
DOI: 10.1103/physrevd.100.074012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of color on rapidity gap survival

Abstract: We study the probability for no jets with transverse momenta above a given cut to be found in the rapidity region between two high PT jets with a large rapidity separation. Our investigation uses the parton shower event generator Deductor with color beyond the leading-color-plus approximation included perturbatively.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In Ref. [9], we examined the effect of color on the rapidity gap survival fraction for a range of y 12 andp T . We found that the effect of having up to two powers of V iπ was always quite small.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Ref. [9], we examined the effect of color on the rapidity gap survival fraction for a range of y 12 andp T . We found that the effect of having up to two powers of V iπ was always quite small.…”
Section: Resultsmentioning
confidence: 99%
“…It also allows us to test whether exponentiation of the iπ contributions makes a substantial numerical difference compared to simply keeping just a small number of factors of V iπ . For this purpose, we will use the gap fraction, for which we have found previously that the inclusion of color beyond the LC+ approximation can be numerically important [9].…”
Section: Assembling the Showermentioning
confidence: 99%
See 3 more Smart Citations